1986
DOI: 10.1111/j.1439-0310.1986.tb00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Counting Behavior by Rats in a Simulated Natural Environment

Abstract: Three experiments were performed to explore the rat's ability to count objects in its environment. Previous research demonstrating counting behavior in animals has typically involved overtraining or extreme motivational conditions in which food or safety were at a premium. In the present experiments, a simulated natural environment was employed in which rats were required to enter a particular tunnel in an array of six to obtain food. Spatial, olfactory and visual cues were controlled so that selection of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…The apparatus and task in the present study were modeled after Davis and Bradford (1986), in which rats were trained to respond to a specific tunnel ordinal position in a row of tunnels. Both variants of the apparatus allow rats to encounter object stimuli in multiple ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparatus and task in the present study were modeled after Davis and Bradford (1986), in which rats were trained to respond to a specific tunnel ordinal position in a row of tunnels. Both variants of the apparatus allow rats to encounter object stimuli in multiple ways.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently rats can discriminate the number of reinforced runs in a runway (Capaldi & Miller, 1988;Burns, Goettl, & Burt, 1995), the number of touches to their body (Davis, MacKenzie, & Morrison, 1989), the number of auditory tones (Davis & Albert, 1986;Breukelaar & Dalrymple-Alford, 1998), the number of electrical foot shocks (Davis & Memmott, 1983), and the number of lined tunnels in an open field (Davis & Bradford, 1986;Suzuki & Kobayashi, 2000). These studies controlled some physical aspects of the stimuli, such as total duration of a tone or spatial positions of tunnels, to prevent them from being used as effective discriminative cues.…”
mentioning
confidence: 99%
“…Rats are capable of learning to enter a target tunnel solely on the basis of its ordinal position in an array of 6 (Davis & Bradford, 1986) or 18 (Suzuki & Kobayashi, 2000) items. Honey bees are able to find a food source located between the third and the fourth position along a series of four identical, equally spaced landmarks (Chittka & Geiger, 1995).…”
Section: Ordinal Reasoningmentioning
confidence: 99%
“…For example, it has been reported that rats can discriminate the number of reinforced runs in a Electronic supplementary material The online version of this article (doi:10.3758/s13420-016-0209-2) contains supplementary material, which is available to authorized users. straight runway (Capaldi & Miller, 1988), the number of touches to their body (Davis, MacKenzie, & Morrison, 1989), the number of auditory tones (Breukelaar & Dalrymple-Alford, 1998;Davis & Albert, 1986), and the number of lined tunnels in an open field (Davis & Bradford, 1986;Suzuki & Kobayashi, 2000). However, excluding an exceptional study, which tested the transfer of numerical discrimination of auditory stimuli to visual stimuli and showed no sign of transfer of learning (Davis & Albert, 1987), the abstractness of numerical concepts in rats has not been elucidated because the clear transfer of counting behavior to novel stimuli has not yet been documented in rats.…”
mentioning
confidence: 99%